APPLICATIONS OF DENDROCHRONOLOGY IN NORTHWESTERN MEXICO. Issue 1 (14th December 2017) - Turkon, Paula; Manning, Sturt W.; Griggs, Carol; Santos Ramírez, Marco Antonio; Nelson, Ben A.; Torreblanca Padilla, Carlos; Wild, Eva Maria
Abstract : Although dendrochronological methods have the potential to provide precise calendar dates, they are virtually absent in Mesoamerican archaeological research. This absence is due to several long-standing, but erroneous, assumptions: that tree rings in this region do not reflect annual growth and environmental variability, that an adequate number of samples do not exist, and that tree-ring measurements cannot be useful without modern trees to link prehispanic chronologies. In this article we present data from the sites of La Quemada and Los Pilarillos, located in the Malpaso Valley, Zacatecas, to demonstrate that suitable archaeologically derived samples of dendrochronologically useful species do exist, that the samples from these sites are measurable and cross-datable, and that the tree rings can yield precise calendar dates using a method that "wiggle-matches" radiocarbon dates on tree-ring sequences. The work demonstrates the potential of these methods to address chronological, and, in the future, climatic questions, which have so far eluded archaeological work in the region. Abstract : Los métodos dendrocronológicos tienen el potencial de proporcionar fechas de calendario precisas, sin embargo son escasamente utilizados en las investigaciones arqueológicas Mesoamericanas. Esto se debe a la existencia de varios supuestos de larga permanencia, pero erróneos tales como: que los anillos de los árboles en esta región no reflejan el crecimiento anual y la variabilidad medioambiental, que no existe un número adecuado de muestras, y que las mediciones de los anillos de los árboles no pueden ser útiles sin la existencia de árboles modernos para vincular las curvas prehispánico. En este artículo, se presentan datos de los sitios de La Quemada y Los Pilarillos, localizados en el Valle de Malpaso, Zacatecas, para demostrar que existen muestras arqueológicas dendrocronológicamente adecuadas, medibles, que se pueden " cross-date ", y que se pueden obtener fechas precisas usando un método llamado "calibración de radiocarbono de secuencias definidas" ( radiocarbon wiggle-matching ). El trabajo pone en evidencia el potencial de estos métodos para abordar cuestiones cronológicas, y en el futuro, también climáticas, las cuales hasta la fecha han eludido el trabajo arqueológico en la región.